Penentuan Skala Prioritas Penanganan Ruas Jalan Provinsi di Kabupaten Purwakarta - Asep Setiawan (Lembaga Layanan Pendidikan Tinggi Wilayah IV, 2019)
The provincial roads maintenance and repair are often constrained by limited budgets, so that the road management priority is generally determined by policy factors, which often cause roads treatment disparity. The purpose of this study was to determine the criteria and sub-criteria, the weights of criteria and sub-criteria, as well as develop a mathematical equation in order to determine to roads handling priority in the area of Purwakarta, West Java. Tha Delphi and Cut Off Point methods were applied to determine the criteria, which result in three criteria selected i.e. road condition, traffic volume and economic factors, respectively. Afterward, the Analytical Hierarchy Process was used to determine the weighting factors for the criteria and sub-criteria. The results for the criteria weights were as follows: the roads conditions had a weighting factor of 67.7%; the traffic volume of 18.3%; and the economi of 13.0%. Based on the criteria and sub-criteria weight, a mathematical equation was develop to define the handling priority of roads in Purwakarta.